Electrode sheet, preparation method thereof and battery
By applying gel polymer layers on both sides of the active material layer of the electrode sheet, the problem of frequent wrinkles during coating and rolling of the electrode sheet is solved, and the stability and performance of battery manufacturing are improved.
Patent Information
- Application Number
- CN202210804008.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-07-07
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2042-07-07
AI Technical Summary
The existing electrode sheets frequently wrinkle during coating and rolling, resulting in manufacturing difficulties and unstable battery performance.
The electrode sheet design is designed to coat the active material layer and the gel polymer layer on the current collector surface. By adding gel polymer layers on both sides of the active material layer, the occurrence of wrinkles during coating and rolling is reduced.
Effectively reduce the incidence of wrinkles during coating and rolling, improve the manufacturing stability and performance of the battery, especially in terms of energy density and cycle stability.
Smart Images

Figure CN117410439B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of batteries, and in particular to an electrode plate and a preparation method thereof, and a battery. Background Art
[0002] With the rapid development and continuous progress of society, energy shortage and environmental pollution problems are becoming increasingly serious, and people's demand for clean energy is becoming increasingly urgent. At the same time, the increasing popularity of new energy vehicles and the increasing development of energy power have prompted people to develop lithium-ion batteries with higher energy density and high safety. At present, lithium-ion power batteries are mostly using lithium iron phosphate and ternary materials, but due to the continuous improvement of energy density and safety performance requirements.
[0003] As the market continues to increase the energy density of battery cells, the space utilization rate of battery cells is also getting higher and higher. The thickness of foil has become thinner and thinner from 10μm and 8μm at the beginning to 6μm and 5μm in mass production now. In addition, the compaction density of positive or negative active materials is getting higher and higher. The compaction density of graphite is generally 1.6g / cm 3 This has caused the manufacturing process to become increasingly difficult, with frequent wrinkles on the pole pieces during coating and rolling, causing manufacturing difficulties for the subsequent die-cutting and winding assembly processes. Summary of the invention
[0004] Therefore, the technical problem to be solved by the present invention is to overcome the defect that the electrode plate in the prior art frequently wrinkles during coating and rolling, thereby providing an electrode plate and a preparation method thereof and a battery.
[0005] To this end, the present invention provides an electrode plate, including a current collector, an active material layer coated with active material on the surface of the current collector, and a polymer layer coated with gel polymer on the surface of the current collector and on both sides of the active material layer.
[0006] In the present invention, the current collector may be a conventional metal foil, such as but not limited to copper foil, aluminum foil, and the like.
[0007] Furthermore, the electrode plate satisfies at least one of the following AD:
[0008] A. The ratio of the width of the polymer layer to the width of the active material layer is 1:40-400, preferably 1:40-200;
[0009] B. The distance between the polymer layer and the active material layer is 0-0.5 mm;
[0010] C. The surface density of the active material layer is 18-35 mg / cm 2 The surface density of the polymer layer is 1.8-2.4 mg / cm 2 ;
[0011] D. An uncoated empty foil area is provided on the current collector on a side of the polymer layer away from the active material layer. Preferably, the width of the empty foil area is 17-19 mm.
[0012] Exemplarily, the width of the active material layer is 200-600 mm, and the width of the polymer layer is 1.5-5 mm.
[0013] Furthermore, the gel polymer is polymerized by acrylonitrile monomers under the action of an initiator.
[0014] Furthermore, based on 100wt% of the total mass of the raw materials, the raw materials of the gel polymer include: 0.5-2wt% of acrylonitrile monomer, 3-5wt% of initiator and 30-95wt% of solvent.
[0015] Optionally, the acrylonitrile monomer is selected from at least one of acrylonitrile, cycloacrylonitrile, 2-bromoacrylonitrile, 3,3-diphenylacrylonitrile and 2-ethoxyacrylonitrile;
[0016] Optionally, the initiator is selected from at least one of benzoyl peroxide, tert-butyl benzoyl peroxide, methyl ethyl ketone peroxide, azobisisobutyronitrile and azobisisoheptanenitrile;
[0017] Optionally, the solvent is selected from at least one of ethylene carbonate, dimethyl carbonate and ethyl methyl carbonate.
[0018] Illustratively, a mixture of ethylene carbonate (EC), dimethyl carbonate (DMC), and ethyl methyl carbonate (EMC) may be used.
[0019] Furthermore, the raw material of the gel polymer further comprises a lithium salt. Optionally, the lithium salt is selected from at least one of lithium hexafluorophosphate and lithium bistrifluoromethylsulfonyl imide (LiTFSI); optionally, in the raw material of the gel polymer, the mass content of the lithium salt is 0.5-2%.
[0020] Furthermore, the electrode plate is a positive electrode plate or a negative electrode plate.
[0021] Furthermore, the active material is selected from at least one of graphite, lithium cobalt oxide, lithium manganese oxide, lithium iron phosphate, lithium nickel cobalt aluminum oxide, lithium nickel manganese oxide, lithium nickel cobalt oxide and lithium nickel cobalt manganese oxide.
[0022] The active material layer in the present invention can be made of conventional raw materials, and in addition to the active material, it can also include conventional binders, conductive agents and other materials. For example, the conductive agent can be but not limited to carbon black, Ketjen black, carbon nanotubes, etc.; the binder can be but not limited to carboxymethyl cellulose (CMC), polyvinylidene fluoride, polyacrylic acid, polytetrafluoroethylene, etc.
[0023] Furthermore, in terms of weight, the active material layer comprises: 90-97 parts of active material, 1-5 parts of conductive agent and 1-5 parts of binder.
[0024] The present invention also provides a method for preparing any of the above-mentioned electrode sheets, comprising:
[0025] Step S1, preparing an electrode slurry containing an active material and a polymer layer slurry containing a gel polymer;
[0026] Step S2, coating the electrode slurry on the current collector and coating the polymer layer slurry on the current collector surface and on both sides of the electrode slurry coating area, forming an active material layer and a polymer layer after drying to obtain the electrode pole piece.
[0027] Preferably, the solvent in the electrode slurry is selected from at least one of water and N-methylpyrrolidone;
[0028] Preferably, the solid content of the electrode slurry is 45-80%.
[0029] For example, the electrode slurry can be prepared by homogenizing in a conventional manner, for example, after mixing the active material, the conductive agent and the binder, adding a solvent, and mixing them evenly under stirring.
[0030] Furthermore, the viscosity of the electrode slurry is 3000-20000cp (25°C).
[0031] Furthermore, the preparation method of the polymer layer slurry includes mixing acrylonitrile monomer, solvent and initiator and then subjecting the mixture to polymerization reaction, or mixing acrylonitrile monomer, lithium salt, solvent and initiator and then subjecting the mixture to polymerization reaction.
[0032] Preferably, the polymerization reaction temperature is 60-90° C., and the reaction time is at least 5 minutes (eg, 5-10 minutes).
[0033] Furthermore, in step S2, the drying temperature is 60-90°C.
[0034] Furthermore, in step S2, the compaction density of the roller is 1.6 to 1.8 g / cm 3 .
[0035] In the present invention, the coating method can be to first coat the front side of the current collector with the existing conventional technology, and then coat the back side of the current collector with the same slurry and process after drying, or to coat both sides at the same time. Among them, the specific implementation method of the present invention adopts the former to coat and form the electrode sheet.
[0036] The present invention also provides a battery, comprising any of the electrode plates described above or an electrode plate prepared by any of the preparation methods described above.
[0037] The technical solution of the present invention has the following advantages:
[0038] 1. The electrode plate provided by the present invention comprises a current collector, an active material layer coated with an active material on the surface of the current collector, and a polymer layer coated with a gel polymer on the surface of the current collector and on both sides of the active material layer. By adding a polymer layer coated with a gel polymer on both sides of the active material layer of the battery cell, the incidence of adverse events such as wrinkles that occur during coating and rolling can be effectively reduced.
[0039] 2. The electrode plate provided by the present invention adopts a gel polymer formed by polymerization of acrylonitrile monomers under the action of an initiator, and especially controls the mass percentage of acrylonitrile monomers, initiators and solvents in the raw materials of the gel polymer. On the basis of maintaining good electrical properties such as battery capacity and cycle stability, the incidence of adverse events such as wrinkles during coating and rolling can be further reduced.
[0040] 3. The method for preparing the electrode sheet provided by the present invention is to control the ratio of the width of the polymer layer to the width of the active material layer to be 1:40-400, especially 1:40-200, or to control the surface density of the active material layer to be 18-35 mg / cm 2 The surface density of the polymer layer is 1.8-2.4 mg / cm 2 , which can further reduce the incidence of adverse events such as wrinkles during coating and rolling.
[0041] 4. In the preparation method of the electrode plate provided by the present invention, the raw material of the gel polymer also includes lithium salt, and especially when the mass content of lithium salt in the raw material of the gel polymer is controlled to be 0.5-2%, the incidence of adverse events such as wrinkles occurring during coating and rolling can be further reduced. BRIEF DESCRIPTION OF THE DRAWINGS
[0042] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0043] Figure 1 Schematic diagram of the structure of the negative electrode sheet in Example 1;
[0044] Figure 2The negative electrode sheet (not coated with polymer) prepared in Comparative Example 1 and the negative electrode sheet (coated with polymer) prepared in Example 1 after rolling, the left side is Comparative Example 1, and the right side is Example 1;
[0045] Figure 3 The discharge performance of the battery cell assembled with the negative electrode sheet prepared in Comparative Example 1 (the negative electrode sheet is not coated with a conductive polymer) and the negative electrode sheet prepared in Example 1 (the negative electrode sheet is coated with a conductive polymer) at different rates;
[0046] Figure 4 The charging performance of the battery cell assembled with the negative electrode sheet prepared in Comparative Example 1 (the negative electrode sheet is not coated with a conductive polymer) and the negative electrode sheet prepared in Example 1 (the negative electrode sheet is coated with a conductive polymer) at different rates;
[0047] Figure 5 The discharge performance of the battery cell assembled with the negative electrode sheet prepared in Comparative Example 1 (the negative electrode sheet is not coated with a conductive polymer) and the negative electrode sheet prepared in Example 1 (the negative electrode sheet is coated with a conductive polymer) at different temperatures;
[0048] Figure 6 The cell cycle performance after assembling the negative electrode sheet prepared in Comparative Example 1 (the negative electrode sheet is not coated with a conductive polymer) and the negative electrode sheet prepared in Example 1 (the negative electrode sheet is coated with a conductive polymer);
[0049] Reference numerals:
[0050] 1. Active material layer; 2. Polymer layer; 3. Empty foil area. DETAILED DESCRIPTION
[0051] The following examples are provided for a better understanding of the present invention, but are not intended to limit the best mode of implementation, nor to limit the content and protection scope of the present invention. Any product identical or similar to the present invention obtained by anyone under the inspiration of the present invention or by combining the features of the present invention with other prior arts shall fall within the protection scope of the present invention.
[0052] If no specific experimental steps or conditions are specified in the examples, the conventional experimental steps or conditions described in the literature in the field can be used. If no manufacturer is specified for the reagents or instruments used, they are all conventional reagent products that can be obtained commercially.
[0053] Example 1
[0054] This embodiment provides a negative electrode plate, such as Figure 1As shown, it includes a current collector, an active material layer coated with active material on the surface of the current collector, and a polymer layer coated with gel polymer on the surface of the current collector and on both sides of the active material layer, the spacing between the active material layer and the polymer layer is 0 mm, and an uncoated empty foil area is provided on the side of the current collector located away from the active material layer, the width of the active material layer is 600 mm, the width of the polymer layer is 3 mm, and the width of the empty foil area is 17 mm.
[0055] This embodiment also provides a method for preparing a negative electrode sheet, comprising the following steps:
[0056] (1) Natural graphite, a conductive agent (conductive carbon black), and a binder (sodium carboxymethyl cellulose) were weighed and mixed in a mass ratio of 96.5:1.0:2.5, and wet mixed and homogenized with water as a solvent to obtain a negative electrode slurry with a solid content of 50%.
[0057] (2) 1 kg of acrylonitrile, 15 kg of ethylene carbonate (EC), 40 kg of dimethyl carbonate (DMC) and 40 kg of ethyl methyl carbonate (EMC) were mixed and stirred in a stirrer to obtain a clear solution. Then 1 kg of LiTFSI was added and stirred to obtain a clear glue solution. Then 3 kg of azobisheptanenitrile was added and polymerized at 60° C. for 5 minutes to obtain a polymer layer slurry.
[0058] (3) Using a copper foil with a thickness of 6 μm as the current collector, an extrusion coater was used to apply the negative electrode slurry and the polymer layer slurry to the middle area of the current collector surface and the two side areas abutting the middle area, respectively, and dried in a tunnel oven at 70°C to form an active material layer and a polymer layer. During coating, the coating scraper was adjusted so that the surface density of the active material layer after drying was 20 mg / cm 2 The surface density of the polymer layer is 2 mg / cm 2 The electrode is rolled after coating, and the compaction density is 1.6g / cm 3 , and you get the negative electrode.
[0059] Example 2
[0060] The present embodiment provides a negative electrode plate, which includes a current collector, an active material layer coated with an active material on the surface of the current collector, and a polymer layer coated with a gel polymer on the surface of the current collector and on both sides of the active material layer, the two being 0.5 mm apart, and an uncoated empty foil area being provided on the side of the current collector located away from the active material layer, the width of the active material layer is 400 mm, the width of the polymer layer is 5 mm, and the width of the empty foil area is 18 mm.
[0061] This embodiment also provides a method for preparing a negative electrode sheet, comprising the following steps:
[0062] (1) Natural graphite, a conductive agent (conductive carbon black), and a binder (sodium carboxymethyl cellulose) were weighed and mixed in a mass ratio of 97.0:1.0:2.0, and wet mixed and homogenized with water as a solvent to obtain a negative electrode slurry with a solid content of 60%.
[0063] (2) 2 kg of 2-bromoacrylonitrile, 53 kg of dimethyl carbonate (DMC) and 40 kg of ethyl methyl carbonate (EMC) were mixed and stirred evenly, and 5 kg of azobisheptanenitrile was added. The mixture was polymerized at 90° C. for 10 minutes to obtain a polymer layer slurry.
[0064] (3) Using a copper foil with a thickness of 6 μm as the current collector, the negative electrode slurry and the polymer layer slurry were respectively coated on the middle area of the current collector surface and the two side areas 0.5 mm away from the middle area by an extrusion coater, and dried in a 60°C tunnel oven to form an active material layer and a polymer layer. During coating, the gap between the coating scraper was adjusted so that the surface density of the active material layer after drying was 18 mg / cm 2 The surface density of the polymer layer is 2.2 mg / cm 2 The electrode is rolled after coating, and the compaction density is 1.6g / cm 3 , and you get the negative electrode.
[0065] Example 3
[0066] The present embodiment provides a negative electrode plate, which includes a current collector, an active material layer coated with an active material on the surface of the current collector, and a polymer layer coated with a gel polymer on the surface of the current collector and on both sides of the active material layer, the spacing between the two is 0 mm, and the current collector is provided with an uncoated empty foil area on the side of the polymer layer away from the active material layer, the width of the active material layer is 600 mm, the width of the polymer layer is 3 mm, and the width of the empty foil area is 17 mm.
[0067] This embodiment also provides a method for preparing a negative electrode sheet, comprising the following steps:
[0068] (1) Natural graphite, a conductive agent (conductive carbon black), and a binder (sodium carboxymethyl cellulose) were weighed and mixed in a mass ratio of 96.5:1.0:2.5, and wet mixed and homogenized with water as a solvent to obtain a negative electrode slurry with a solid content of 50%.
[0069] (2) 1 kg of acrylonitrile, 16 kg of ethylene carbonate (EC), 40 kg of dimethyl carbonate (DMC) and 40 kg of ethyl methyl carbonate (EMC) were mixed and stirred evenly, 3 kg of azobisheptanenitrile was added, and polymerization reaction was carried out at 60° C. for 5 minutes to obtain a polymer layer slurry.
[0070] (3) Using a copper foil with a thickness of 6 μm as the current collector, an extrusion coater was used to apply the electrode slurry and the polymer layer slurry to the middle area of the current collector surface and the two side areas abutting the middle area, respectively, and dried in a tunnel oven at 70°C to form an active material layer and a polymer layer. During coating, the gap between the coating blades was adjusted so that the surface density of the active material layer after drying was 20 mg / cm 2 The surface density of the polymer layer is 2 mg / cm 2 The electrode is rolled after coating, and the compaction density is 1.6g / cm 3 , and you get the negative electrode.
[0071] Example 4
[0072] This embodiment provides a negative electrode plate and a method for preparing the same, the only difference being that the width of the polymer layer is 1.5 mm.
[0073] Example 5
[0074] The present embodiment provides a positive electrode plate, which includes a current collector, an active material layer coated with an active material on the surface of the current collector, and a polymer layer coated with a gel polymer on the surface of the current collector and on both sides of the active material layer, the spacing between the two is 0 mm, and the current collector is provided with an uncoated empty foil area on the side of the polymer layer away from the active material layer, the width of the active material layer is 600 mm, the width of the polymer layer is 3 mm, and the width of the empty foil area is 17 mm.
[0075] This embodiment also provides a method for preparing a positive electrode sheet, comprising the following steps:
[0076] (1) The positive electrode material (molecular formula: lithium iron phosphate LiFeP, manufacturer: Defang Nano, model: DY-2) and SP (carbon black conductive agent) and PVDF (polyvinylidene fluoride) are mixed by a wet method in a mass ratio of 96:2:2 with NMP as solvent to obtain a positive electrode slurry with a solid content of 50%.
[0077] (2) 1 kg of acrylonitrile, 15 kg of ethylene carbonate (EC), 40 kg of dimethyl carbonate (DMC) and 40 kg of ethyl methyl carbonate (EMC) were stirred in a stirrer to obtain a clear solution, and then 1 kg of LiTFSI was added and stirred to obtain a clear glue solution, and then 3 kg of azobisheptanenitrile was added and polymerized at 60° C. for 5 minutes to obtain a polymer layer slurry.
[0078] (3) Using an aluminum foil with a thickness of 6 μm as the current collector, the positive electrode slurry and the polymer layer slurry were respectively coated on the middle area of the current collector surface and the two side areas abutting the middle area by an extrusion coater, and dried in a tunnel oven at 70°C to form an active material layer and a polymer layer. During coating, the gap between the coating scraper was adjusted so that the density of the active material layer after drying was 40 mg / cm 2 The surface density of the polymer layer is 2 mg / cm 2 The electrode is rolled after coating, and the compaction density is 1.6g / cm 3 , and you get the positive electrode.
[0079] Comparative Example 1
[0080] This embodiment provides a negative electrode plate, which includes a current collector and an active material layer coated with an active material on the surface of the current collector, and uncoated empty foil areas are provided on both sides of the current collector located at the active material layer. The width of the active material layer is 600 mm, and the width of the empty foil area is 20 mm.
[0081] This embodiment also provides a method for preparing a negative electrode sheet, comprising the following steps:
[0082] (1) Natural graphite, a conductive agent (conductive carbon black), and a binder (sodium carboxymethyl cellulose) were weighed and mixed in a mass ratio of 96.5:1.0:2.5, and wet mixed and homogenized with water as a solvent to obtain a negative electrode slurry with a solid content of 50%.
[0083] (2) Using a copper foil with a thickness of 6 μm as the current collector, the electrode slurry was coated on the middle area of the current collector surface by an extrusion coater and dried in a tunnel oven at 70°C to form an active material layer. During coating, the gap between the coating blade was adjusted so that the density of the active material layer after drying was 20 mg / cm 2 The negative electrode sheet after coating is rolled and the compaction density is 1.6g / cm 3 , and you get the negative electrode.
[0084] Experimental Example 1
[0085] According to the methods of the embodiments and comparative examples, 20,000 meters of negative electrode sheets or positive electrode sheets were manufactured respectively, and the length of wrinkles was counted to calculate the incidence rate of wrinkles = wrinkle length / 20,000×100%.
[0086] Table 1 Length and incidence of wrinkles
[0087] project Length of folds / m Incidence / % Example 1 60 0.3 Example 2 160 0.8 Example 3 180 0.9 Example 4 140 0.7 Example 5 200 1.0 Comparative Example 1 310 1.6
[0088] It can be seen from the above table that compared with Comparative Example 1, the negative electrode sheets and positive electrode sheets prepared in Examples 1-5 of the present invention can significantly reduce the incidence of wrinkles, especially Example 1. Compared with Examples 2 and 3, Example 1 has a shorter length of wrinkles due to the addition of lithium salt in the preparation of the gel polymer. Compared with Example 4, Example 1 has a shorter length of wrinkles due to controlling the ratio of the width of the polymer layer to the width of the active material layer within a preferred range. Compared with Example 1 and Example 5, it can be seen that compared with the positive electrode sheet, the negative electrode sheet can further reduce the incidence of wrinkles.
[0089] Experimental Example 2
[0090] The negative electrode sheets obtained in Example 1 and Comparative Example 1 were respectively prepared into battery cells according to the following method: the positive electrode material (molecular formula: LiFeP, manufacturer: Defang Nano, model: DY-2) was uniformly mixed with SP (carbon black conductive agent) and PVDF (polyvinylidene fluoride) in a mass ratio of 96:2:2 to prepare a slurry, and the slurry was coated on an aluminum foil (surface density of 40 mg / cm 2 ), and after drying, roller pressing is performed to obtain the positive electrode sheet, and the electrolyte is a mixture of EC and DMC in a volume ratio of 1:1 and sodium hexafluorophosphate (concentration of 1 mol / L), and a PE diaphragm is used. After assembly, welding of the pole ears and the top cover, and injection of liquid, a battery cell is obtained.
[0091] The battery cells assembled from the negative electrode sheets of Example 1 and Comparative Example 1 were tested on a battery tester as follows:
[0092] (1) Charge and discharge performance test at different rates: 25°C, 0.5C constant current and constant voltage charging to 3.65V, current cut-off at 0.05C, discharge at different rates, 0.33C / 1C / 1.5C.
[0093] (2) Charge and discharge performance test at different temperatures: Normal temperature, 25℃ 0.5C constant current and constant voltage charging to 3.65V, current cut-off at 0.05C, the battery cell reaches temperature equilibrium at different temperatures (-20℃, 25℃, 45℃), and 1C discharge to 2.0V.
[0094] (3) Cycle test: Step 1: Normal temperature, 25°C, 0.5C constant current and constant voltage charging to 3.65V, current 0.05C cut-off, Step 2: Stand for 15 minutes, Step 3: 1C discharge to the lower limit voltage 2.0V. Step 4: Stand for 15 minutes. Cycle test from step 1 to step 4. Stop the test until the discharge capacity is 80% of the initial capacity.
[0095] Results Figure 2-6 As shown in the attached figures, it can be seen that the battery cell formed by Example 1 of the present invention also has good rate performance and cycle performance, and can reduce the occurrence of wrinkles.
[0096] Experimental Example 3
[0097] The negative electrode sheets obtained in Examples 1-4 and Comparative Example 1 were taken and prepared into battery cells according to the method of Experimental Example 2, respectively, and were recorded as experimental groups 1-4 and a control group, respectively. The positive electrode sheet obtained in Example 5 and the negative electrode sheet prepared according to the method of Comparative Example 1 were taken, and EC and DMC with a volume ratio of 1:1 were combined with sodium hexafluorophosphate (concentration of 1 mol / L) as the electrolyte, and a PE diaphragm was used. The battery cells were assembled, the pole ears and the top cover were welded, and the liquid was injected to obtain battery cells, which were recorded as experimental group 5. The discharge specific capacity and 500-cycle capacity retention rate at 1C were tested on a battery tester according to the method of Experimental Example 2. The results are shown in the table below.
[0098] Table 2 Electrical performance results
[0099]
[0100] It can be seen from the above table that the deviations in discharge specific capacity and capacity retention rate between the test groups 1-5 of the present invention and the control group are all less than 1%, that is, there is no significant difference, indicating that the test groups of the present invention can significantly improve the coating and rolling wrinkles without affecting the battery rate, cycle and safety performance. In particular, the discharge specific capacity and capacity retention rate measured values of the test group 1 are improved compared with those of the control group.
[0101] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived therefrom are still within the scope of protection of the invention.
Claims
1. An electrode plate, characterized in that: The invention comprises a current collector, an active material layer coated with an active material on the surface of the current collector, and a polymer layer coated with a gel polymer on the surface of the current collector and on both sides of the active material layer; the ratio of the width of the polymer layer to the width of the active material layer is 1:40-200; the spacing between the polymer layer and the active material layer is 0 mm; the surface density of the active material layer is 18-35 mg / cm 2 The surface density of the polymer layer is 1.8-2.4 mg / cm 2 ; Based on the total mass of the raw materials as 100wt%, the raw materials of the gel polymer include: 0.5-2wt% of acrylonitrile monomer, 3-5wt% of initiator and 93-96.5wt% of solvent, the raw materials of the gel polymer also include lithium salt, and the mass content of lithium salt in the raw materials of the gel polymer is 0.5-2%, and the active material layer and the polymer layer are respectively coated on the middle area of the surface of the collector and the two side areas abutting the middle area.
2. The electrode plate according to claim 1, characterized in that: An uncoated empty foil area is disposed on the current collector at a side of the polymer layer away from the active material layer.
3. The electrode plate according to claim 2, characterized in that: The width of the empty foil area is 17-19 mm.
4. The electrode plate according to claim 1, characterized in that: The gel polymer is polymerized by acrylonitrile monomers under the action of an initiator.
5. The electrode plate according to claim 1, characterized in that: The acrylonitrile monomer is at least one selected from acrylonitrile, cycloacrylonitrile, 2-bromoacrylonitrile, 3,3-diphenylacrylonitrile and 2-ethoxyacrylonitrile.
6. The electrode plate according to claim 1, characterized in that: The initiator is selected from at least one of benzoyl peroxide, tert-butyl benzoyl peroxide, methyl ethyl ketone peroxide, azobisisobutyronitrile and azobisisoheptylnitrile.
7. The electrode plate according to claim 1, characterized in that: The solvent is selected from at least one of ethylene carbonate, dimethyl carbonate and ethyl methyl carbonate.
8. The electrode plate according to claim 1, characterized in that: The lithium salt is selected from at least one of lithium hexafluorophosphate and lithium bis(trifluoromethylsulfonyl)imide.
9. The electrode plate according to claim 1, characterized in that: The electrode plate is a positive electrode plate or a negative electrode plate; and / or, the active material layer includes: 90-97 parts of active material, 1-5 parts of conductive agent and 1-5 parts of binder; and / or, the active material is selected from at least one of graphite, lithium cobalt oxide, lithium manganese oxide, lithium iron phosphate, lithium nickel cobalt aluminum oxide, lithium nickel manganese oxide, lithium nickel cobalt oxide and lithium nickel cobalt manganese oxide.
10. A method for preparing an electrode sheet according to any one of claims 1 to 9, characterized in that: include: Step S1, preparing an electrode slurry containing an active material and a polymer layer slurry containing a gel polymer; Step S2, coating the electrode slurry on the current collector, coating the polymer layer slurry on the surface of the current collector and on both sides of the electrode slurry coating area, forming an active material layer and a polymer layer after drying, and rolling to obtain the electrode plate.
11. The method for preparing an electrode sheet according to claim 10, characterized in that: The solvent in the electrode slurry is selected from at least one of water and N-methylpyrrolidone; and / or the solid content of the electrode slurry is 45-70%.
12. The method for preparing an electrode sheet according to claim 10, characterized in that: The preparation method of the polymer layer slurry comprises the steps of mixing acrylonitrile monomer, lithium salt, solvent and initiator and subjecting the mixture to polymerization reaction to obtain the polymer layer slurry.
13. The method for preparing an electrode sheet according to claim 10, characterized in that: The polymerization temperature is 60-90°C and the time is at least 5 minutes.
14. A battery, characterized in that: It includes the electrode sheet described in any one of claims 1 to 9 or the electrode sheet prepared by the preparation method described in any one of claims 10 to 13.
Citation Information
Patent Citations
Lithium ion polymer secondary battery and its manufacturing method
JP2004207118A
Nonaqueous electrolyte secondary battery
JP2009117162A